2010
DOI: 10.1002/cncr.25303
|View full text |Cite
|
Sign up to set email alerts
|

Deoxycitidine kinase is associated with prolonged survival after adjuvant gemcitabine for resected pancreatic adenocarcinoma

Abstract: BACKGROUND: Gemcitabine (2 0 ,2 0 -difluorodeoxycytidine) administration after resection of pancreatic cancer improves both disease-free survival (DFS) and overall survival (OS). Deoxycytidine kinase (dCK) mediates the ratelimiting catabolic step in the activation of gemcitabine. The authors of this report studied patient outcomes according to the expression of dCK after a postoperative gemcitabine-based chemoradiation regimen. METHODS: Fortyfive patients with resected pancreatic adenocarcinoma received adjuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 84 publications
(163 reference statements)
3
47
0
Order By: Relevance
“…27 They also categorically demonstrated that a low dCK expression was an independent risk factor for recurrence and mortality. Two recent retrospective studies have also signified the fact that a preoperative high level of dCK protein is able to predict patient response to gemcitabine and is associated with an improved outcome for these patients in way of increased OS.…”
Section: Discussionmentioning
confidence: 98%
“…27 They also categorically demonstrated that a low dCK expression was an independent risk factor for recurrence and mortality. Two recent retrospective studies have also signified the fact that a preoperative high level of dCK protein is able to predict patient response to gemcitabine and is associated with an improved outcome for these patients in way of increased OS.…”
Section: Discussionmentioning
confidence: 98%
“…The expression of these nucleoside transporters is correlated with chemosensitivity and patient survival [19][20][21][22][23]. After being taken into the cells, gemcitabine is activated by deoxycytidine (dCK) [24,25]. Thus, hENT1, hCNT1, hCNT3, and dCK positively contribute to gemcitabine activity and to cancer cells' sensitivity to gemcitabine.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, A549 cells expressing shRNAs targeting GFP or DCK were seeded for proliferation assays according to the 3T3 protocol in absence of drug or presence of dFdC (10 nM) (right panel). Error bars denote SD of triplicate independent experiments outcome in patients with resected pancreatic cancer who received dFdC as adjuvant therapy [30,32]. Moreover, a recent study reported that the quantitative analysis of DCK mRNA using FFPE tissue samples can be used to predict the sensitivity to gemcitabine-based adjuvant therapy in patients with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%